Daun Bungkus dan Hegemoni Kaum Laki-laki: Riset Etnografi di Masyarakat Irarutu, Papua Barat - Setia Pranata; Tri Juni Angkasawati; Rachmalina Prasodjo (Antropologi Indonesia, 2020)
Sexual behavior among Papuans known as unique. One of the unique sexual behavior that can be found is a bungkus “wrap”. Bungkus is the traditional technology to enlarge the male genitals using leaves which Papuans known as daun tiga jari. Hegemony and the value of masculinity that characterize sexual activity, expressed in order to wrap up behavior. These activities is to make as strong men to do sexual activity. That is not a myth. As the embodiment of the values of masculinity, wrap done by male and adolescent. As a behavior, action to wrap up not free from health risks. Packaging is not really going to result in damage to the genitals. Unsafe sexual behavior people who are wrapped, at risk for sexually transmitted diseases and HIV / AIDS. Recognition of female sex workers due to the use of wrappers is an indication of this risk. Socially, the phenomenon wrap also are at risk of Domestic Violence. Meanwhile, the Government is not doing more related to the bungkus phenomenon a lot done Papuans. All that will make Papuans in Kaimana expressive sexual behavior as vulnerable people.